ANALISIS NILAI HASIL TERHADAP WAKTU PADA PROYEK KONTRUKSI (STUDI KASUS PADA PROYEK REHABILITASI IRIGASI GLAPAN TIMUR) - Rafilah, Widam; Sutarto, Agung (DAS Institute, 2023)
The public's need for building projects is increasing along with Indonesia's economic expansion. In order to realize building projects that can produce the best results, serious management is needed. One way of effective time management to support project implementation on schedule is through the application of the Earned Value Analysis approach. This research aims to analyze the application of Earned Value Analysis to estimate the final project completion time every week in order to find out whether it is in accordance with the initial project schedule plan. In addition, to determine the value of Earned Value Analysis in the completion and percentage of the value of construction projects in the 2022 fiscal year. This research method is descriptive qualitative using the Earned Value Analysis approach. The results showed that the difference between the estimated time from the baseline, project realization, and the planned schedule reached -36.21 and EVA analysis also showed a significant increase in the percentage of completion of each job each month, compared to the planned schedule. Keywords: Rate of Results, Time, Construction Project